Nonvascularized human skin chronic allograft rejection. Issue 11 (13th August 2019) - Rotman, Samuel; Koch, Nathalie; Wiesner, Lucie; Aubert, Vincent; Rosales, Ivy A.; Colvin, Robert B.; Raffoul, Wassim; Pascual, Manuel
Abstract : A 65‐year‐old man had extensive burns of the lower legs in 1991, at the age of 40 years. He was treated by nonvascularized and de‐epithelialized, allogeneic split‐thickness skin allograft and cyclosporine monotherapy for 2 months. Ulcers developed between 10 and 25 years after transplantation and a surgical debridement on the lower extremities was required. Analyses of the removed tissue allografts showed chronic antibody‐mediated and cellular rejection with extensive and dense fibrosis, and diffuse capillary C4d deposits. An anti‐DRB1*08:01, donor‐specific antibody was present. A unique clinical condition with late immunopathological features of human skin chronic allograft rejection is reported. Abstract : This report describes the clinical and pathological features of human chronic skin allograft rejection.